Chapter 6. Mulching - Stephen M. Olson (EDIS, 2006)
Polyethylene mulch has been used for commercial vegetable production in Florida for more than 30 years (Fig. 6-1). There are approximately 70,000 acres of mulched vegetables in Florida, ranking it near the top in the U.S. for this production method. Almost all of the tomato and strawberry production is on mulch. Other crops that have considerable production on mulch are pepper, eggplant and various melons. Other crops such as squash, cucumbers or cauliflower have lesser acreage on mulch or are grown in a double crop situation. This document is HS715, one of a series of the Horticultural Sciences Department, UF/IFAS Extension. Original publication date June 1995. Revised November 2006.